Implementasi Framework CodeIgniter dalam Perancangan Aplikasi E-Commerce Berbasis Website (Studi Kasus: Tiara Brand) - Andarweni, Dhea; Triayudi, Agung; Iskandar, Agus (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Tiara Brand is a self-produced clothing business. The process of selling products at Tiara Brand is done by promoting their products through social media. This process is considered less effective, because customers have to order through another application, namely WhatsApp. Business owners also find it difficult to promote their products widely. Based on these problems, this study will discuss the design and creation of a website-based e-commerce application using the CodeIgniter framework, so that it is easier for customers to buy products from Tiara Brand, because it can be done on the same website. In addition, business owners can also more easily manage each transaction and can promote their products to customers without regional restrictions. the steps of this research are made in the form of a flowchart and go through stages consisting of; 1) Data collection, 2) Literature study, 3) Design, 4) Program code preparation, and 5) Application testing and using the String Matching Algorithm as an implementation of the application being built. The results of the research are the construction of a website that not only displays the products being sold, but can also be used for transactions and has the potential to develop Tiara Brand selling online.
Keywords: Implementation; CodeIgniter Framework; E-Commerce Applications; Website